Comparative Analysis of Erythrocyte Proteomes of Water Buffalo, Dairy Cattle, and Beef Cattle by Shotgun LC-MS/MS - Guo, Jiaying; Sun, Yali; Tian, Yu; Zhao, Junlong (Frontiers in Veterinary Science, 2019)
A number of researches demonstrate that Babesia orientalis (B. orientalis) can only infect water buffalo (Bubalus bubalis), instead of dairy cattle (Bos taurus) and beef cattle (Bos taurus), even though three of them all belong to the tribe of Bovini and have close evolutionary relationships. In addition, Babesia species are intracellular protozoan, that obligating parasitized in erythrocytes. It may indicate that the infect specificity may due to the differences of erythrocytes proteins. 491, 1143 and 1145 proteins were identified from water buffalo, beef cattle and dairy cattle by searching the database in uniprot and NCBI, respectively. The number of identified proteins of water buffalo was far less than that of beef cattle and dairy cattle, particularly in the range from 15 to 25 kDa. Remarkably, 290 identified proteins were unique to water buffalo, of which putative gamma-globin and putative epsilon-globin were significantly possible to be relevant with the B. orientalis survival only in water buffalo. According to GO annotation, total of 2222 proteins were annotated in terms of molecular function, biological process and cellular component. The number of proteins in oxygen binding of water buffalo were far more than beef cattle and dairy cattle. This is the first time to comparative analyze the protein profiles of water buffalo, beef cattle and dairy cattle. The unique expressed proteins in water buffalo obtained in this study may give new insights into the mechanism of B. orientalis infection exclusively in water buffalo and may be benefit for develop the strategies against B. orientalis.